Love Your Mother : 50 States, 50 Stories, and 50 Women United for Climate Justice - McDuff, Mallory D. (Broadleaf Books, 2023)
As a mother and a professor of environmental education, Mallory McDuff wanted to give her two daughters and her students a roadmap to engage in climate justice in their communities, rather than be left feeling paralyzed by the enormity of the problem. She set out to find women of diverse ages, backgrounds, and vocations - one from each of the fifty US states - as inspiration for a new kind of leadership focused on the heart of the climate crisis. Love Your Mother lifts up the stories of these women working toward a viable future, from farmer and rancher Donna Kilpatrick in Arkansas to writer Latria Graham in South Carolina.From Alabama to Alaska, from Wisconsin to Wyoming, these women are poets, physicians, climate scientists, students, farmers, writers, documentary filmmakers, and more.